Peningkatatan Bahasa Inggris Menggunakan Digital Vocabularies Bagi Pemuda–Pemudi Desa Ancaran Kabupaten Kuningan - Nani Ronsani Thamrin; Erlan Darmawan; Fadia Nur Fazriah; Rina Risnawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2022)
The development of science, the opening of unlimited access to information, the enactment of the free market have an impact on the need to prepare the young generation of this nation to be ready to face its era. So equipping the younger generation, especially for educators who will provide knowledge to their students with English language skills using Digital Vocabularies is something that must be done in the current era of the covid-19 pandemic. This service activity is carried out with the aim of fostering interest in learning English and improving the quality of English for young people in Ancaran Village, Kuningan Regency, besides helping lower economic communities gain access to learning English, especially young people so that it can be implemented in the learning process. they are at school. Socialization is carried out through discussions between the implementers of community service activities and young people. After that, the implementers of the community service program will be implemented the use of digital vocabularies into the English learning process Keyword: digital, vocabularies, language, English, learning